2017
DOI: 10.15640/jpbs.v5n1a5
|View full text |Cite
|
Sign up to set email alerts
|

Resilience among Students from the Majority and Minority Group: The Israeli Case

Abstract: The current study examined levels of individual, community and national resilience as well as resilience protective and suppressing factors among Israeli Jewish (majority group) and Israeli Arab (minority group) students. Results indicated that Israeli Jewish students reported higher levels of individual, community and national resilience scale scores compared with Israeli Arab students. However, when resilience was measured as strength to vulnerability ratio, only individual resilience was significant. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…The current article described a new shortened self‐report scale for determining national resilience (NR‐13). We based the NR‐13 on earlier, longer national resilience scales employed in Israeli studies (Kimhi et al., ; Kimhi et al., ; Kimhi, Dror, & Sapir, ). Two different studies examined the structure and validity of the NR‐13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current article described a new shortened self‐report scale for determining national resilience (NR‐13). We based the NR‐13 on earlier, longer national resilience scales employed in Israeli studies (Kimhi et al., ; Kimhi et al., ; Kimhi, Dror, & Sapir, ). Two different studies examined the structure and validity of the NR‐13.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, national resilience has been assessed by a 25‐item scale in Israeli studies of coping with different adversities (Kimhi, Dror, & Sapir, ; Kimhi, Goroshit, & Eshel, ). National resilience has positively been predicted by sense of coherence (SOC), well‐being, and higher economic conditions (Eshel & Kimhi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirroring findings of studies of US minority groups [ 8 , 36 , 37 , 38 ], studies conducted in Israel to compare the resilience of Arab minority communities and that of the Jewish dominant group showed that Arab children and adults reported lower resilience and well-being in face of trauma, political violence, and mass casualties [ 39 , 40 , 41 ]. These studies suggested that members of the Arab minority have fewer economic, political, and socio-cultural resources, making them more vulnerable to adversity [ 39 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…We will measure resilience by conducting interviews and pre- and postsurveys with plot owners. Our survey includes replication of an instrument developed by Kimhi and colleagues [ 37 ] to examine three different dimensions of resilience in majority-minority groups—individual, community, and ethnic origin–based resilience—taking into consideration protective and suppressing factors that shape a sense of resilience.…”
Section: Introductionmentioning
confidence: 99%